PENATALAKSANAAN PENCETAKAN LINGGIR DENGAN JARINGAN FLABBY MENGGUNAKAN SENDOK CETAK FISIOLOGIS MODIFIKASI - Selamat Suhardi Butarbutar; Ismet Danial Nasution (Journal of Syiah Kuala Dentistry Society, 2019)
Introduction: Flabby ridge compromise support, retention and stability of complete dentures. Thepresence of flabby ridge tends to create a difficulty while making complete dentures. Many impressiontechniques have been proposed to overcome these difficulties. Objectives: This paper aims to explainan impression technique on flabby ridge anterior mandibular using modified final impression tray withtwo tunnels. Case Description: An 80-years-old female patient using complete dentures. She wasconcerned that her lower complete denture was loose. On clinical examination there was anteriorflabby ridge from canine to canine of the mandibular arch. The technique described in this case wasusing clear swapolimerized acrylic resin with two tunnels for final impression tray, using polivynilsiloxane light body impression was injected around the flabby ridge using a dispensing gun from oneside of the tunnel, taking care that the flow to the opposite side was controlled by the clear custom tray,to ensure minimal distortion on flabby tissue and coverage of impression material on all edentulousarea. Discussion: Flabby ridge is a challenge in prosthodontics to achieve stability and retention ofcomplete dentures. Provision of complete dentures in patient with flabby ridge can be managed bycorrect impression method. By using this modified final tray, it will not displace the flabby tissue thatcan dislodge the denture, simple custom tray, easy to practice and less time. Conclusion: Choosingappropriate impression technique and used the right final impression tray may increase patientsprosthesis stability and retention.Keywords: Flabby Ridge, Modified Impression Tray, Clear Swapolimerized Acrylic Resin